a-phase tantalum film deposition using bipolar high-power impulse magnetron sputtering technique - CHO MIN GYEONG; Kang, Unhyeon; Lim, Sang Ho; Han, Seunghee (Elsevier Sequoia, 2023)
In this study, a method for forming a highly adhesive and ductile α-phase tantalum film on 304 stainless steel using the bipolar high-power impulse magnetron sputtering (bipolar HiPIMS) technique was investigated. The growth of brittle β-phase tantalum, which is commonly formed when using conventional direct current magnetron sputtering methods (DCMS) at room temperature, was prevented by the high-energy ions directed toward the growing films. The results showed the formation of an extremely thin (<70 nm) α-phase tantalum film without any additional processes, such as substrate biasing or heating. In addition, a high adhesion strength exceeding 45 MPa, broadened intermixed layer, and nanocrystalline microstructure were achieved by the effect of positive voltage. These results indicate that the bipolar HiPIMS technique is a facile deposition method for modifying the substrate surface and forming high-quality crystalline films. Our tantalum films are optimized to protect substrates against corrosion in severely harsh mechanical, chemical, and thermal environments. To confirm the superiority of the bipolar HiPIMS technique over HiPIMS and DCMS, the properties of the films formed using the three methods were analyzed via X-ray diffraction, Auger electron spectroscopy, atomic force microscopy, scanning electron microscopy, and pull-off adhesion testing.